2006
DOI: 10.1016/j.ydbio.2006.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Laminar organization of the early developing anterior hypothalamus

Abstract: The bHLH-PAS transcription factor SIM1 is required for the development of neurons of the anterior hypothalamus (AH). In order to dissect this developmental program, we compared gene expression in the AH of E12.5 Sim1(+/+) and Sim1(-/-) littermates using an oligonucleotide-based microarray. Our analysis identified 48 genes that were downregulated and 8 genes that were upregulated. We examined the expression pattern of 10 of the identified genes--Cart, Cbln1, Alcam, Unc-13c, Rgs4, Lnx4, Irx3, Sax1, Ldb2 and Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 29 publications
4
60
0
1
Order By: Relevance
“…Another possible explanation for this selective compensatory activity of Ldb2 may relate to its levels of expression (Caqueret et al, 2006), which may not be sufficient to fully compensate for Ldb1 loss at all developmental stages and in all cell types. Our experiments indicate that, in the RPCs, Ldb2 is sufficient to mediate Lhx2 activity, whereas studies in the limb bud show that Ldb2 is necessary for Isl1 activity (Tzchori et al, 2009;Narkis et al, 2012).…”
Section: The Unequal Role Of Ldb1 and Ldb2 In Retinogenesismentioning
confidence: 99%
“…Another possible explanation for this selective compensatory activity of Ldb2 may relate to its levels of expression (Caqueret et al, 2006), which may not be sufficient to fully compensate for Ldb1 loss at all developmental stages and in all cell types. Our experiments indicate that, in the RPCs, Ldb2 is sufficient to mediate Lhx2 activity, whereas studies in the limb bud show that Ldb2 is necessary for Isl1 activity (Tzchori et al, 2009;Narkis et al, 2012).…”
Section: The Unequal Role Of Ldb1 and Ldb2 In Retinogenesismentioning
confidence: 99%
“…Hypothalamic neurogenesis occurs between embryonic day 10 (E10) and E16, with individual hypothalamic nuclei typically being generated in an outsideinside sequence (Ifft, 1972;Altman and Bayer, 1986). Apparently, a lateromedial gradient exists along the whole hypothalamus, and possibly a dorsoventral gradient (Ifft, 1972;Wyss and Sripanidkulchai, 1985;Caqueret et al, 2005Caqueret et al, , 2006McClellan et al, 2006McClellan et al, , 2008, and this neurogenetic activity is still observed in the adult (Kokoeva et al, 2005). In the chick, two phases in the neurogenesis of the hypothalamus have been defined.…”
Section: Hypothalamic Subdivisions: Comparative Aspectsmentioning
confidence: 99%
“…The transcription factors Sim1, Arnt2, and Otp are coexpressed in this anterior hypothalamic portion and are essential for terminal differentiation of the neurosecretory neurons (Michaud et al, 1998(Michaud et al, , 2000Acampora et al;1999;Wang and Lufkin, 2000;Hosoya et al, 2001). One of their common downstream genes, Brn2, is necessary for the differentiation of the cells producing oxytocin, vasopressin, and CRH, whereas Sim2, a paralog of Sim1, contributes to the expression of TRH and somatostatin genes (Caqueret et al, 2006). Inactivation of any of these genes results in the elimination of the paraventricular and supraoptic structures and neuroendocrine hormone expression (reviewed in Markakis, 2002).…”
Section: Supraoptoparaventricular Areamentioning
confidence: 99%
“…In contrast to the restricted influence of SF-1 on VMH development, loss of nkx2.1 (Titf1) results in severe disruption of the entire hypothalamus except for the most ventral aspect as evidenced by an altered or absent expression pattern of SF-1, Sim-1, and Pax-6 (Marin et al, 2002). Other transcription factors on our list include ldb2, which has been linked to hypothalamic development (Caqueret et al, 2006) and Fezf1 (Hirata et al, 2006), COUP-TFII (Tripodi et al, 2004), and Satb2 (Britanova et al, 2005), which are all implicated broadly in neural development. Although the functional relevance of these other transcription factors in the VMH remains to be determined, it is likely that they will participate in specifying VMH patterning or cell fate.…”
Section: The Neonatal Mouse Vmh Transcriptomementioning
confidence: 99%